Decision to Use Digital Payment Systems in Perspective of Behavioral Financial Theory (Universitas Terbuka, 2023)
Digital payment is a payment method as a forerunner to innovation due to digitalization. Digitalization is driven by rapid technological developments, where these developments cause changes in people's mindsets and habits. The decision to use digital payments, within the Behavioral Financial Theory framework, is predicted to be influenced by financial literacy and inclusion. Behavioral Financial Theory studies individual behavior in understanding, analyzing, and managing finances to make the right decisions to avoid financial problems, including decisions about using digital payment systems. This study aims to determine the effect of financial literacy and inclusion on decisions to use digital payment systems in the perspective of behavioral financial theory. The study was conducted on active Business Administration Study Program Faculty of Social and Political Sciences University of Jember students in odd semester of the 2022/2023 academic year. Based on a quantitative approach, using multiple linear regression analysis method, the study results prove that financial inclusion influences the decision to use a digital payment system, while financial literacy does not. These results indicate that individual financial literacy raises awareness to behave in a way that maintains a stable, secure, and prosperous financial condition in managing their finances.